The consequences of Brugia malayi infection on the flight and energy resources of Aedes aegypti mosquitoes - Somerville, Alastair G. T. (Sci Rep, 2019)
Evidence from experimental infection studies has shown that infected mosquitoes exhibit altered host-seeking behaviours, with suppression and activation of behaviours dependent on the parasite’s development stage. The mechanisms are poorly characterised; however, infections can impact mosquito energy reserves, thereby influencing key life-history traits and behaviours. In addition, filarial infection is likely detrimental to flight due to damage caused by developing worms. This study aimed to evaluate the impacts of Brugia malayi infection on Aedes aegypti flight parameters: distance, average speed, maximum speed and number of flight bursts, using a tethered flight mill. In addition, we explored whether differences in flight capacity may be due to the effect of infection on glycogen and lipid reserves. Infection with filarial worms significantly reduced flight distance but increased the number of flight bursts. Exposure to microfilaermic blood led to a significant decrease in average and maximum flight speeds even in the absence of an established infection. Mosquitoes fed on microfilaraemic blood showed reduced levels of glycogen (−37.9%) and lipids (−49.7%) compared to controls at nine days post-exposure. However, a one-hour period of flight activity caused an increase in lipid content for both infected and control mosquitoes. Consequential flight incapacitation may serve in explaining the heterogeneous distribution of lymphatic filariasis.